Comparative genomics of freshwater Fe-oxidizing bacteria: implications for physiology, ecology, and systematics - Emerson, David; Field, Erin; Chertkov, Olga; Davenport, Karen; Goodwin, Lynne; Munk, Christine; Nolan, Matt; Woyke, Tanja (Frontiers in Microbiology, 2013)
The two microaerophilic, Fe-oxidizing bacteria Sideroxydans ES-1 and Gallionella ES-2 have single circular chromosomes of 3.00 and 3.16 Mb that encode 3049 and 3006 genes, respectively. Multi-locus sequence analysis confirmed the relationship of these two organisms to one another, and indicated they may form a novel order, the Gallionellalaes, within the Betaproteobacteria. Both are adapted for chemolithoautotropy, including pathways for CO2-fixation, and electron transport pathways adapted for growth at low O2-levels, an important adaptation for growing on Fe(II). Both genomes contain Mto-genes implicated in iron-oxidation, as well as other genes that could be involved in Fe-oxidation. Nearly 10% of their genomes are devoted to environmental sensing, signal transduction, and chemotaxis, consistent with their requirement for growing in narrow redox gradients of Fe(II) and O2. There are important differences as well. Sideroxydans ES-1 is more metabolically flexible, and can utilize reduced S-compounds, including thiosulfate, for lithotrophic growth. It has a suite of genes for nitrogen fixation. Gallionella ES-2 contains additional gene clusters for exopolysaccharide production, and has more capacity to resist heavy metals. Both strains contain genes for hemerythrins and globins, but ES-1 has an especially high numbers of these genes that may be involved in oxygen homeostasis, or storage. The two strains share homology with the marine FeOB Mariprofundus ferrooxydans PV-1 in CO2 fixation genes, and respiratory genes. In addition, ES-1 shares a suite of 20 potentially redox active genes with PV-1, as well as a large prophage. Combined these genetic, morphological, and physiological differences indicate that these are two novel species, Sideroxydans lithotrophicus ES-1T (ATCC 700298T; JCM 14762; DSMZ 22444; NCMA B100), and Gallionella capsiferriformans ES-2T (ATCC 700299T; JCM 14763; DSMZ 22445; NCMA B101).